Efektivitas Pengolahan Limbah Domestik di Instalasi Pengolahan Air Limbah (IPAL) Suwung-Denpasar, Bali - Rarasari, Desak Made Goldyna; Restu, I Wayan; Ernawati, Ni Made (Journal of Marine and Aquatic Sciences; Vol 5 No 2 (2019), 2018)
Denpasar City and Badung Regency has a very large population growth rate, diversity, and intensity of development activities that produced domestic waste which if not properly managed, causes burden and damage to the aquatic environment. Wastewater Treatment Plant (WWTP) Suwung-Denpasar is one of the wastewater treatment business for waste management center from the area around Denpasar, Sanur, and Kuta. Based on the data analysis was known that the waste generated has not been appropriate environmental quality standards so that will affect the quality of the water. The aim of his research is to investigate the effectiveness of domestic wastewater treatment conducted in March - April 2017 by observation method in process and effectiveness measurement of waste water treatment. The processing begins with the distribution of waste in Denpasar and Sanur areas that are channeled to the bar screen and then collected to the inflow pumping station to be channeled to the receiving tank including waste from the Kuta area. Subsequent waste flows into the chamber grit to be filtered and taken to the aeration pond for 2 days then to the sedimentation pool for 16 hours and flowed to the effluent canal. The results showed the percentage of effective waste treatment in oil and fat restoration 85%, detergent 62%, and BOD 57%, while not effective in ammonia change because only reduced 26%, DO and H 2 S are not in accordance with environmental quality standards.